1998
DOI: 10.1136/jech.52.6.385
|View full text |Cite
|
Sign up to set email alerts
|

Maternal and infant health problems after normal childbirth: a randomised controlled study in Zambia

Abstract: Study objectives-The main aim of the study was to discover if a midwife home visiting programme has a significant effect on the prevalence of health problems and breast feeding behaviour of mothers who delivered normally and their healthy fullterm newborn babies, during a period of 42 days after delivery. Another aim was to compare the mothers', the midwife's, and the doctor's findings of prevalence of health problems at the end of the puerperium period. Design-A randomised controlled trial was carried out. On… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
1

Year Published

2003
2003
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(32 citation statements)
references
References 23 publications
2
29
1
Order By: Relevance
“…The type of health problems the women reported in this study is comparable with those in other studies, [10][11][12][13]15 but there are large differences in frequency of occurrence. This can be ascribed to the differences in study populations and the methods used to elicit health problems.…”
Section: Discussionsupporting
confidence: 80%
“…The type of health problems the women reported in this study is comparable with those in other studies, [10][11][12][13]15 but there are large differences in frequency of occurrence. This can be ascribed to the differences in study populations and the methods used to elicit health problems.…”
Section: Discussionsupporting
confidence: 80%
“…The results are also in line with an extensive literature on home visiting programmes and face-to-face counselling aimed to improve maternal care and parenting, in both developed [16][17][18][19] and developing countries [20][21][22][23][24], including cultural minorities in the former [25,26]. Some authors have found that most of the positive effects were concentrated in higher risk subgroups [27].…”
Section: Discussionsupporting
confidence: 84%
“…Nevertheless, the conclusion regarding reduced mortality remained stable even after we included two such trials 32,33 from developing countries (Zambia 32 and the Syrian Arab Republic 33 ). Upon assuming that all deaths in these two trials occurred in the neonatal period, the pooled RR of We depicted both random-effects and fixed-effects model estimates for completeness; however, we preferred a random-effects model because substantial heterogeneity (I 2 > 50%) was observed for neonatal mortality.…”
Section: Strengths and Limitationsmentioning
confidence: 99%